Additional distal femoral osteotomy for insufficient correction after high tibial osteotomy. (27th August 2018) - Nakamura, Ryuichi; Kuroda, Kazunari; Takahashi, Masaki; Katsuki, Yasuo
Abstract : A 70-year-old man who was treated with a closed-wedge high tibial osteotomy (HTO) had recurrent right medial knee pain 12 years after the initial osteotomy. We planned a recorrection osteotomy because the patient led an active lifestyle, had well-preserved range of motion and the lateral compartment was still intact. According to preoperative deformity analysis, which indicated a tibia in slight valgus and a femur in moderate varus, recorrection of the distal femur was chosen. Seven degrees of biplanar distal femoral osteotomy (DFO) was performed using a contralateral version of the TomoFix Medial Distal Femur. At 1 year follow-up, the femorotibial angle had improved from 178° to 170°, and the Japanese Orthopaedic Association score had improved from 75 to 95 points. Additional DFO could be a viable alternative for total knee arthroplasty or recorrection HTO when the centre of the deformity is located at the distal femur.